2014
DOI: 10.1016/j.procs.2014.08.038
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Unnecessary Laboratory Testing Using Health Informatics Applications: A Case Study on a Tertiary Care Hospital

Abstract: BACKGROUND: Like many healthcare resources, laboratory testing has been over-utilized for years with a huge number of unnecessary lab tests being done. The elimination of unnecessary laboratory testing is becoming more and more important in the control and management of the rapid growth of healthcare costs. OBJECTIVES: To develop a quantitative tool to identify unnecessary laboratory tests, based on quantitative over-utilization, and recommend a plan of control based on results and findings. METHODS: The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Discouraging unnecessary tests such as CDU must be a multi-pronged approach by both the user and a system approach [18]. A user approach is focused on altering the physician user behavior by emphasizing the importance of eliminating unnecessary CDU or other diagnostic testing and the cost as well as potential downstream harmful procedures that may result.…”
Section: Possible Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Discouraging unnecessary tests such as CDU must be a multi-pronged approach by both the user and a system approach [18]. A user approach is focused on altering the physician user behavior by emphasizing the importance of eliminating unnecessary CDU or other diagnostic testing and the cost as well as potential downstream harmful procedures that may result.…”
Section: Possible Solutionsmentioning
confidence: 99%
“…Rather than just immediate feedback, this points to the need for more aggressive measures. A more intensive effort at physician education could be used to isolate a department, specialty or a physician more likely to utilize excess testing [18].…”
Section: Possible Solutionsmentioning
confidence: 99%
“…1,2 An area of particular concern is the ordering of investigations; 3 the number of required tests increased from 6% to 8% from 2004 to 2014. 4,5 Diagnostic laboratory tests impose more fi nancial diffi culties and lead to poor patient satisfaction with services by causing morbidities like polyphlebotomy and hospitalacquired anaemia.…”
Section: Introductionmentioning
confidence: 99%
“…Recognising over utilised laboratory tests and developing strategies to improve physician ordering behaviour in requesting diagnostic tests in the form of utilisation review programmes and behavioural change are considered priorities in health systems in every country, particularly developing countries. 1,9,10 Previous literature suggested that unnecessary tests might be due to a wide range of reasons, including a poor physician awareness of how to use and interpret laboratory tests, 11,12 lack of clinical guidelines, 6,13 inadequate supervision during bedside rounds, 14 unawareness of test costs 15 and fear of legal issues. 16 Accordingly, strategies to change physician ordering behaviour range from providing feedback, 17 changing laboratory test formats, 18 providing physicians with information about test costs, 19,20 and utilising clinical guidelines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation